Rational objective law A reflection on the spiritual illumination compatible with the nature of things, as the basis of the validity of Law - Mahdi Shahabi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2023)
Louis Le Fur's thought should be seen as a symbol of the interaction of metaphysics and reality; The duality that finds another interpretation in Le Fur's language, that is, natural law and objective law. The requirement of the mentioned interaction is not to consider Le Fur's philosophical framework as rationalism or Kantian philosophy and to consider Aristotelian philosophy as the origin of Le Fur's thought. However, Le Fur's natural law seems to have taken its validity from the traditional rationality that is based on tainted wisdom; A rationality that can be considered as its inherent spiritual or spiritual illumination. Therefore, Le Fur's enlightenment should not be considered an experimental enlightenment, like the enlightenment of philosophers such as Petrazyski and GényIn his analysis of the basis of the validity of his natural law, Le Fur is so close to his contemporary traditionalists such as René Guénon that he states that man is the God`s Caliph. Any legal concept that does not consider the eternal soul of man in his analysis cannot be evaluated as a correct perception.However, unlike the same traditionalists, Le Fur does not give a role to revelation in the objectification of the concept of natural law and justice. He does not evaluate the transition from Catholic jurisprudence to Protestantism negatively. Le Fur's concern is the synthesis of metaphysics and reality.But, without a doubt, what Le Fur means by this metaphysics is not human metaphysics; rather it considers divine metaphysics. Therefore, one should not think about the transition from Catholic jurisprudence to Protestantism. We know that traditionalists like Guénon consider the transition from Catholic jurisprudence to Protestantism as the meaning of passing traditional rationality.Nevertheless, his belonging to perennial wisdom has not hindered his empirical methodological approach to the compatibility of natural law with the nature of things and has not led to Shari'a voluntarism as an all-round ideology.Apparently, it remains at the level of mere general ideology, and this generality, in addition to opening the way for Le Fur's experimental method, also leaves unanswered the fundamental question that when the divine legislative will has no role in detailing the perennial law, so in which direction perennial wisdom is supposed to guide a person?It seems that Aristotelian philosophy has clarified its task concerning perennial wisdom. By removing the divine legislative will, Aristotle practically accepts that evolution should be left to the hands of history and the passage of time; the approach and result that Le Fur has not been able to get rid of.The fact is that Le Fur's type of law is a symbol of evolutionary experience, and from this point of view, its basis should be sought in the nature of Aristotelian objects. It seems that these types of law fulfill the function of objectifying or objectifying traditional rationality. It plays a role in Le Fur's legal thinking. It is clear that such a position for the nature of things, in order to interact and synthesize with traditional rationality, is not acceptable in traditionalist thought such as Guénon.Interestingly, by adopting the experimental method, Le Fur also comes to the conclusion that there is superhuman rationality that guides the world; and that man is not only the mind; it does not just matter. Man is both material and mental, and for Le Fur, it is surprising why the experimental method of positivists is unable to see and verify such realities.Despite this, the result of the synthesis of Le Fur's metaphysics and empirical reality is very limited, and practically, perennial Le Fur's wisdom, from the perspective of a humanist view, will not seek a different interpretation of the nature of Aristotelian objects. In other words, by relying on it, you cannot be a watcher of Catholic jurisprudence. But, on the one hand, it is possible to avoid falling into the trap of the empirical illumination of philosophers like Petrazyski;The drawback of empirical illumination is that it does not open an evolutionary path for the transition from Sien to Sollen. There is a possibility that he may regress and sometimes evaluate slavery as favorable; it is difficult to separate it from public opinion and it leads nowhere.On the other hand, relying on Le Fur's thought, it is possible to establish a philosophy of law in which law is neither a captive of pure materialism nor is it caught in Kant's subjectivism, which synthesizes the hierarchical system of law with empirical reality does not wantA result can also be achieved in the framework of the nature of Aristotelian objects. According to its evolutionary approach, Aristotelian philosophy cannot deny the law of Le Fur and accepts it. Le Fur's thought in the field of contract does not have a different result compared to Aristotelian philosophy. In Le Fur's contract, like the Aristotelian contract, the principle of the sovereignty of the will is not the rule in order to result in a practically positivist justice.